Cultivating a Culture of Patient Safety in Healthcare Settings: A Systematic Review of Evidence-Based Interventions - Dardas, Lubna; Al-Hussami, Mahmoud (South Eastern European Journal of Public Health, 2024)
Background and purpose: Establishing a robust culture of safety is essential for enhancing health outcomes and minimizing risks to patients. This systematic review aims to synthesize interventions designed to enhance safety culture in healthcare settings. Methods: A comprehensive literature search was performed across multiple databases, including PubMed, CINAHL, and Scopus. The initial search yielded a total of 250 articles. After applying inclusion and exclusion criteria, which considered study design, population, and intervention type, 35 articles were shortlisted for full-text review. Ultimately, 21 studies met the final inclusion criteria, focusing on various interventions aimed at promoting safety culture. Results: The analysis revealed notable variation in the types of safety culture interventions implemented across the studies, with educational programs emerging as the most frequently adopted approach. The effectiveness of these interventions was found to be significantly influenced by both individual and systemic factors, highlighting the importance of contextual elements in promoting safety culture. Additionally, many interventions faced challenges related to sustainability and maintaining long-term impact, suggesting that ongoing support and resources are necessary for success. The review also indicated that the participation of nursing professionals in safety culture initiatives was often limited, despite their critical role in patient care, underscoring the need for strategies that engage this key group more effectively. Conclusion: The review underscores the necessity for targeted strategies that actively engage nursing professionals in safety culture initiatives to foster a safer healthcare environment. The findings serve as a valuable resource for policymakers and healthcare managers aiming to implement best practices for enhancing safety culture.